Welcome to Ryan's World - Shaheen Hosany, Asheeabee R., (SAGE Business Cases., 2021)
The evolution of Ryan "Kaji" (real last name Guan) is captured in this case study as he develops from vlogger to influencer. Ryan had his humble beginnings in 2015, at 3 years old, when he complained to his mother Loann about his non-existent YouTube profile. Loann then uploaded Ryan's first, amateurish toy unboxing video on YouTube. By the time Ryan was eight (2020), he had featured in the Forbes Top Ten List of Highest YouTube Income Earners 3 years in a row. This armchair case follows the Kaji family story, as a mother's hobby progressed to become a multi-million-dollar commercial empire. Growing fast, Ryan's World diversified into multiple YouTube channels and product categories, created its own merchandise, crossed borders, and successfully collaborated with major brands. Along the way, the Ryan brand faced criticisms, including his perceived negative influence on child consumers and allegations of deceptive advertising. The case study encourages readers to ponder on why brand Ryan is so attractive, addictive, and prompts children around the world to emulate him. This case looks at the portrayal of a child, who literally has access to the entire toyshop, and encourages students to explore the concepts of influencer marketing, vlogging, and embedded advertising. Additionally, it further solicits readers to consider some contemporary ethical issues in the contentious child consumer space. This case study combines secondary data with the lead author's extensive research on the behavior of children as consumers, and exposure to Ryan from a parent's perspective. It is designed for use in marketing, consumer behavior, and entrepreneurship modules at both undergraduate and post graduate levels.